Emerging Roles of Circ-ZNF609 in Multiple Human Diseases - Wang, Songbo; Wu, Jiajin; Wang, Zhongyuan; Gong, Zixuan; Liu, Yiyang; Wang, Zengjun (Frontiers in Genetics, 2022)
Circular RNAs (circRNAs) are a special type of endogenous RNAs with extensive roles in multiple human diseases. They are formed by back-splicing of partial sequences of the parental precursor mRNAs. Unlike linear RNAs, their covalently closed loop structure without a 5′ cap and a 3′ polyadenylated tail confers on them high stability and they are difficult to be digested by RNase R. Increasing evidence has proved that aberrant expressions of many circRNAs are detected and that circRNAs exert essential biological functions in disease development and progression via acting as a molecular sponge of microRNA, interacting with proteins as decoys or scaffolds, or self-encoding small peptides. Circular RNA zinc finger protein 609 (circ-ZNF609) originates from exon2 of ZNF609, which is located at chromosome 15q22.31, and it has recently been proved that it can translate into a protein. Being aberrantly upregulated in various diseases, it could promote malignant progression of human tumors, as well as tumor cell proliferation, migration, and invasion. Here in this review, we concluded the biological functions and potential mechanisms of circ-ZNF609 in multiple diseases, which could be further explored as a targetable molecule in future accurate diagnosis and prognosis.